Evaluation of serum level of MicroRNA323-3p, MicroRNA517a and MicroRNA519d in Ectopic pregnancy: a comparative study - Farah Ahmed Dera'a,; Fadia Jassim Alizzi, (Journal of the Pakistan Medical Association, 2024)
Aim: To assess the role of serum micro ribonucleic acids 323-3p, 517a and 519d in the diagnosis of ectopic pregnancy. Method: The case-control study was conducted at the Gynaecology Department of Al-Yarmouk Teaching Hospital, Baghdad, Iraq, from June 1, 2020, to May 1, 2021, and comprised women with ectopic pregnancy in group A, and those with a viable intrauterine pregnancy in group B. Serum samples were taken for beta human chorionic gonadotropin measurement and for micro ribonucleic acids 323-3p, 517a and 519d testing using polymerase chain reaction. Data was analysed using SPSS 24. Results: Of the 100 women with mean age 26.8±5.29 years, 50(50%) were in each of the 2 groups. There was no significant difference between the groups in terms of age, gravida, parity, abortion, and gestational age (p>0.05). The mean beta human chorionic gonadotropin in group B was significantly greater than group A (p=0.001). In group A, micro ribonucleic acid 323-3p expression was significantly higher, mean micro ribonucleic acid 517a expression was significantly lower and mean micro ribonucleic acid 519d expression was significantly lower compared to group B (p<0.05). At micro ribonucleic acid 323-3p cut-off point 2.415, the test accurately distinguished between ectopic and viable pregnancy with 92% sensitivity, 100% specificity and total area under the curve 0.994 (p=0.001). Conclusion: Serum micro ribonucleic acid 323-3p, 517a and 519d might be helpful biomarkers in the diagnosis and follow-up of patients with ectopic pregnancy. Key Words: Pregnancy, Gestational, Gynecology, Ectopic, Chorionic Gonadotropin, Polymerase Chain Reaction, MicroRNAs